Hydrogen to link heat and electricity in the transition towards future Smart Energy Systems. (1st September 2016) - Nastasi, Benedetto; Lo Basso, Gianluigi
Abstract: Nowadays, two fundamental issues are related to the Energy transition towards Future Smart Energy Systems: the design of new high efficiency technological appliances and the use of new Eco-fuels. The crucial challenge is to integrate the increasing share of intermittent RES (Renewable Energy Sources) in National energy mix. Above all, linking both heat and electricity production is the key strategy to face this challenge at urban, regional and national scale. Power-To-Gas application by means of Renewable Hydrogen (H2 ) production would be the viable solution due to H2 has a double application: as a fuel for combustion or chemical conversion as well as an energy storage medium for RES mismatch compensation. In this paper four different H2 -technologies were considered: Hydrogen enriched Natural Gas (H2NG), MHHP (Metal Hydride Heat Pump), GHP (Gas-driven Heat Pump) and SCH4 (Synthetic Methane). An aggregated energy system model was built to assess H2 contribution in PES (primary energy saving). When RES share ranges from 25% to 50%, using H2 for heating purposes avoids the low round trip efficiency of its deferred electricity purpose. If transport excluded, there are no meaningful gains from H2 Ts systems but, they allow to green NG end-uses and decarbonize heating, especially, where NG-Grid is widespread. Highlights: The energy transition, the highlander fossil fuel and the Power to Gas opportunities. An overview of renewable hydrogen technologies for both heating and electricity uses. Modelling the energy system with RES penetration up to 50% of share and Grid Priority. The primary energy savings from renewable hydrogen technologies in the energy systems. The role of electro-fuels in decarbonization between PES and carbon recycling.